2022
DOI: 10.1111/jace.18394
|View full text |Cite
|
Sign up to set email alerts
|

First‐principles investigation of elastic and electronic properties of double transition metal carbide MXenes

Abstract: We use first‐principles‐based density functional theory (DFT) calculations to investigate the structural, elastic, and electronic properties of various pristine and oxygen (O)‐functionalized double transition metal (DTM) MXenes with general formulas of M2′M′′C2 and M2′M′′C2O2, where M′ = Mo, Cr and M′′ = Ti, V, Nb, Ta. The dynamic stability of the DTM MXenes are assessed and elastic stiffness constants (Cij) are used to investigate the mechanical stability and properties of the compositions. The calculated ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 80 publications
(166 reference statements)
0
5
0
Order By: Relevance
“…In addition, the total energy of In 2 O 3 with these vacancies was treated by the density mixing scheme in conjunction with the conjugate gradient technique. During the structural optimization, the lattice parameters and atomic positions of In 2 O 3 with these vacancies were fully relaxed 33–36 …”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the total energy of In 2 O 3 with these vacancies was treated by the density mixing scheme in conjunction with the conjugate gradient technique. During the structural optimization, the lattice parameters and atomic positions of In 2 O 3 with these vacancies were fully relaxed 33–36 …”
Section: Theoretical Methodsmentioning
confidence: 99%
“…During the structural optimization, the lattice parameters and atomic positions of In 2 O 3 with these vacancies were fully relaxed. [33][34][35][36] 3 RESULTS AND DISCUSSIONS…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Meanwhile, in most MXenes, the p-band of carbon/nitrogen is lower than the d-band of transition metals. It is observed that in all the functionalized MXenes discussed, due to higher electronegativity of X (C and N) atoms and connected functional groups compared to transition metals, transition metals become positively charged by losing electrons [30] . Additionally, the electronic properties of monolayer Ti 3 C 2 X 2 (X = F, Cl, Br, I) functionalized with halogen atoms have also been studied.…”
Section: Electronic Propertiesmentioning
confidence: 98%
“…In addition to the structural properties, MXenes also possess other important properties, with metal conductivity being the most significant. All the MXenes exhibit metallic properties without any surface functionalization [30,31] . However, after surface terminal modification, Sc 2 CF 2 , Sc 2 C(OH) 2 , Sc 2 CO 2 , Ti 2 CO 2 , Zr 2 CO 2 , and Hf 2 CO 2 become semiconductors with a bandgap of approximately 0.25-2.0 eV.…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…As seen in Figure a, oxygen functionalized MXenes such as W 3 N 2 O 2 H 2 and Ta 4 C 3 O 2 have higher 2D-stiffness than bare MXenes, W 3 C 2 and Ta 4 C 3 . The strong M–O bond formed due to oxygen functionalization is responsible for the higher 2D-stiffness of oxygen functionalized MXenes. However, as seen in Figure b, the 3D-stiffness of oxygen functionalized and bare MXenes are comparable. In general, MXenes exhibit higher 2D-stiffness than all other classes of 2D materials.…”
mentioning
confidence: 95%